Trend Analysis of Land Change in the Kreo Sub-watershed Jatibarang Reservoir, Semarang City - Andreas Hudisasmoko; Suharyanto; Suprapto (Future Science, 2023)
The arrangement of land systematically and in an integrated manner is an important effort to protect the watersheds. The Jatibarang reservoir in Kreo catchment area also have sedimentation problems, which can be a serious threat to the useful life of the Jatibarang reservoir. The purpose of this study was to analyze the trends of land cover changes in the Jatibarang reservoir watersheds from 1999 to 2020. The assessment of land cover changes based on Landsat 8 satellite image data of the reservoir watersheds area in 1999, 2003, 2010, 2013, 2015, 2018, 2020 collected from the https://earthexplorer.usgs.gov/. The analysis of land cover data using ArcGis Swat software. There was a slight decline of forest area from 1999 to 2010. That was due to the function changes off forest as paddy fields and built-up land. After 2010, there was a degradation of the forest area and paddy fields, followed by a fairly rapid increase in built-up land. The type of built-up land cover increased by ± 308% due to the rate of population growth which resulted in an increase of the need for housing and the growth of industrial area. A slight rate of forest reduction is caused by the needs to provide tourism-related land such as stalls, parking lots and additional tourist facilities. The garden area which decreased until 2010, gradually increasing from 2013 to 2020. This is related to the change in people's tendency to change their livelihood from farming to gardening. It was also observed that in 2020 the waters of the Jatibarang reservoir had decreased. These results indicate that there has been a change in the function of the Jatibarang reservoir land for the needs of the surrounding community.